Clinical validation of a glove with pH indicator (vagitest®) in diagnosis approach of vaginal infection - Tilli, Miguel; Orsini, Adrián; Alvarez, María Marta; Gallardo, Elena; Mormandi, Juan O (Brazilian Journal of Sexually Transmitted Diseases, 2007)
Introduction: cervical vaginal infections (CV) are relevant due to their potential complication both in obstetrics and gynaecologic patients. It has beenestablished that the determination of vaginal pH, by the use of reactive strip, is a simple and inexpensive tool to be applied in the different levels ofmedical care to the diagnosis of these infections. Objective: to estimate the value of sensibility, specificity, predictive positive value and predictivenegative value by self examination of vaginal pH with the use of a glove with pH indicator (Vagitest®). Also, a comparison of the classical methodmade by the physician and the Vagitest® method was made. Methods: One hundred and eighty-one asymptomatic or asymtomatic patients were eva-luated in a prospective way from August 2006 to April 2007. All the patients were derived to gynaecology infectious control office with or without sin-toms of vaginal infection. The recruited patients used Vagitest®before the habitual microbiological procedure for CV that included: vaginal swab formicroscopic examination, pH determination and amine test. The use of the new method consists of introducing a finger into the vagina with the pHindicador and the immediate reading. For the diagnosis of bacterial vaginosis, Amsel and/or Nugent criteria were used. The values obtained by thepatients through self examination with Vagitest®were compared then with the classical measurement with reactive strip made by the physician usingthe speculum and considered gold standard. Statistical analysis: the sensibility, specificity, predictive positive value (PPV) and predictive negativevalue (PNV) were evaluated. Results: the average age of the patients included in this study was 33.59 years (range: 16-70 yrs). Thirty two of the 181patients included were pregnant (17.67) and all of them ran through more than 12 weeks of pregnancy. The most frequent microbiological diagnosiswas habitual microbiota in 90 patients (49.72%) and bacterial vaginosis was the most prevalent vaginal infection (48/181:26.51%). Other diagnosis:vulvovaginal candidiasis in 18 cases (9.99%), intermediate microbiota 11 (6.07%) and trichomoniasis in 5 patients (2.76%). From the 103 patients withincreased pH (> 4.5) with the use of Vagitest®, 91(88.3%) proved to be increased in the conventional measurement with reactive strip (true positives)and only in 12 cases (11.6%) the pH was lower than 4.5 (false positives). Of the 78 women in which the pH with the use of Vagitest ® was lower than4.5, 60 (76.9%) proved to be < 4.5 with the conventional measurement (true negatives) and only in 18 cases (23%) the pH was > 4.5 with reactive strip(true negatives). The sensibility of Vagitest ® was 83.49% (C.I: 95%: 74.89-89.66) and its specificity 83.33% (C.I: 95%: 72.30-90.73). The PPV was88.35% (C.I: 95%: 80.16-93.57), and PNV: 76.92% (CI: 95%: 65.75-85.40). Conclusion: we conclude that this new tool is highly reliable to beapplied in the medical practice by patients or by healthcare provides.